(untitled) (Biological Sciences - PJSIR, 2009)
In present study two types of vegetables, one irrigated with tap and other with sewage water, were analyzed with respect to heavy metals. The concentration of heavy metals was high in sewage, soil, and vegetables than in house source. All metals were not detected except iron (0.07 mg/l) in tap water. The accumulation of Cr in sewage ranged 0.1- 14.1 mg/kg that was maximum in Carrot and minimum in Reddish, while Cd was not detected in Carrot. The concentrations of Mn, Fe and Zn in sewage-irrigated vegetables were more than house holds samples.